The French Cartographer Jacques-Nicolas Bellin's Plans of 18th-century Urban Settlements in Present-Day Canada - Ferley, Paul (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1996)
This research note examines the 18th century plans of five urban settlements located in present-day Canada. These plans were contained in the 18th century atlas, Le Petit Atlas Maritime, by the French cartographer Jacques-Nicolas Bettin. The plans were not only of the French settlements of Québec, Louisbourg and Montréal but also the English settlements of Halifax and St. John's. This note extends the analysis by John W. Reps of the French and English town planning traditions in the New World to exclusively Canadian settlements. The French settlements were influenced both by geography and by decisions taken by their original founders. The English settlement of Halifax was influenced by the formal planning tradition that emerged from the early settlements in the Tidewater colonies of present-day Virginia and Maryland. Geography had a more dominant impact on the plan of St. John's with the harbour shoreline defining what was eventually to become the main thoroughfare in the settlement.